Two Novel Flavin-Containing Monooxygenases Involved in Biosynthesis of Aliphatic Glucosinolates - Kong, Wenwen; Li, Jing; Yu, Qingyue; Cang, Wei; Xu, Rui; Wang, Yang; Ji, Wei (Frontiers in Plant Science, 2016)
Glucosinolates (GSLs), a class of secondary metabolites from cruciferous plants, are derived from amino acids and have diverse biological activities, such as in biotic defense, depending on their side chain modification. The first structural modification step in the synthesis of aliphatic (methionine-derived) GSLs—S-oxygenation of methylthioalkyl GSLs to methylsulfinylalkyl GSLs—was found to be catalyzed by five flavin-containing monooxygenases (FMOs), FMOGS-OX1-5. Here, we report two additional FMOGS-OX enzymes, FMOGS-OX6 and FMOGS-OX7, encoded by At1g12130 and At1g12160, respectively. The overexpression of both FMOGS-OX6 and FMOGS-OX7 decreased the ratio of MT GSL to the sum of MT and MS GSL, suggesting that the introduction of the two genes converted MT GSL into MS GSL. Analysis of expression pattern revealed that the spatial expression of the two genes is quite similar and partially overlapped with the other FMOGS-OX genes, which are primarily expressed in vascular tissue. We further analyzed the responsive expression pattern of all the seven FMOGS-OX genes to exogenous treatment with abscisic acid (ABA), 1-aminocyclopropane-1-carboxylic acid (ACC), jasmonic acid (JA), salicylic acid (SA), indole-3-acetic acid (IAA), and low and high temperatures. Although these genes showed same tendency toward the changing stimulus, the sensitivity of each gene was quite different. The variety in spatial expression among the FMOGS-OX genes while responding to environmental stimulus indicated a complex and finely tuned regulation of GSL modifications. Identification of these two novel FMOGS-OX enzymes will enhance the understanding of GSL modifications and the importance of evolution of these duplicated genes.